HUBUNGAN ANTARA IKLIM ORGANISASI DAN PENGETAHUAN KOMUNIKASI DENGAN PRESTASI KERJA PEGAWAI DINAS PENDIDIKAN KOTA DEPOK - IIN ASIKIN (Jurnal Manajemen Pendidikan, 2011)
This research aims to determine the relationship between: (1) organizational climate with achievement; (2) knowledge of communication with achievement; and (3) the relation between organizational climate and knowledge of communication with achievement. The research method using survey by correlation approach. This research used as a sample of 80 employees, and 20 employees for testing, and selected based on a simple random technique (simple random sampling). The study was conducted at Depok Local Office Education.Technique data collecting was using the instrument in the form of questionnaire. This instrument is calibrated with the test item validity and reliability coefficients. To test the validity of using Pearson Product Moment correlation, while the reliability coefficient is calculated using the formula of Cronbach Alpha. The results showed that: first, there were positive relationship between organizational climate and achievement; secondly, there is a positive relationship between knowledge of communication with achievement; thirdly, there is a positive relationship between organizational climate and knowledge of communication together with achievement.The implication of this research is an effort in improving the achievement can be done through organizational climate and knowledge of communication.